IMPLEMENTASI MODIFIKASI SARANA DAN PRASARANA TERHADAP PENINGKATAN HASIL PEMBELAJARAN PERMAINAN SEPAKBOLA PADA SISWA KELAS VIII SMPN I CIWIDEY KABUPATEN BANDUNG:Penelitian Tindakan Kelas Di SMPN 1 Ciwidey Kecamatan Ciwidey Kabupaten Bandung - Rikrik Rosada, - (2012)
The research was motivated by problems in SMPN Ciwidey is a lack of equipment and infrastructure in learning the game of football. Problems in the study of whether the application of the modification of facilities and infrastructure in games can improve learning outcomes of football matches in the Class VIII student at SMPN 1 Ciwidey . The research objective is a thorough writer who wants to change the infrastructure can improve the application of pupils in class learning game of football VIII in an SMP Ciwidey district. Bandung. The method used is the method of action research in class (PTK). Samples of Class VIII student field SMPN Ciwidey numbered 1 to 25 people. The research instrument used was a test of basic skills basic game is a game of football: passing, dribbling and shooting. Test hypotheses using the Z test and Liliefos normality test. The results of the implementation of the conclusions obtained data processing facilities and infrastructure changes can improve learning outcomes of football games for students of junior high school in the District 1 Class VIII N Ciwidey. Bandung. As a suggestion the process of learning the game of football should use the application for modification of facilities and basic engineering skills of football games DAPT.